2013
DOI: 10.4097/kjae.2013.64.6.511
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of analgesic efficacy between oblique subcostal transversus abdominis plane block and intravenous morphine for laparascopic cholecystectomy. A prospective randomized controlled trial

Abstract: BackgroundThe ultrasound-guided oblique subcostal transversus abdominis plane (OSTAP) block provides a wider area of sensory block to the anterior abdominal wall than the classical posterior approach. We compared the intra-operative analgesic efficacy of OSTAP block with conventional intravenous (IV) morphine during laparoscopic cholecystectomy.MethodsForty adult patients undergoing laparoscopic cholecystectomy under standard general anesthesia, were randomly assigned for either bilateral OSTAP block using 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…It was suggested that the application of TAP block before surgery decreases the peroperative use of opioids remarkably (10). However, we applied TAP block after surgery because we observed, in our preliminary study, that preoperative TAP block, especially in high doses, caused the surgeon to have difficulties in determining the anatomy and prolonged the duration of surgery in upper abdominal operations such as inguinal hernia and varicocele.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the application of TAP block before surgery decreases the peroperative use of opioids remarkably (10). However, we applied TAP block after surgery because we observed, in our preliminary study, that preoperative TAP block, especially in high doses, caused the surgeon to have difficulties in determining the anatomy and prolonged the duration of surgery in upper abdominal operations such as inguinal hernia and varicocele.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation was assessed using a four‐point scale (0: completely alert; 1: sleepy occasionally but rousable; 2: asleep often but rousable; 3: asleep and unrousable) . Nausea and vomiting were assessed using a four‐point scale (0: no nausea and vomiting; 1: slight nausea resolving without treatment; 2: slight nausea and/or vomiting responding to treatment; 3: nausea and/or vomiting not responding to treatment) .…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have shown marginal benefit of TAP blocks in reducing opioid consumption or pain scores. [72][73][74][75] Overall, TAP blocks do not have a routine place in laparoscopic cholecystectomy, given the low pain scores that can be achieved with systemic multimodal analgesia and local anesthetic infiltration of port sites. 72,75 Bariatric surgery Two RCTs have examined the analgesic efficacy of TAP blocks in laparoscopic gastric (roux-en-Y) bypass surgery, with conflicting results.…”
Section: Laparoscopic Cholecystectomymentioning
confidence: 99%